CULTURAL HERITAGE PRESERVATION IN INDIA: SAFEGUARDING A LIVING LEGACY - Pathak, Tribeni; Das, Shikha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
However, keeping this heritage safe is a big challenge. Cities are growing fast and threatening old sites, and climate change is making them decay faster. We are also losing traditional knowledge and making heritage sites too commercial. To address these challenges, we need to work together - government, international partners, local communities, and technology. The government and organizations like UNESCO are helping preserve our heritage. Local communities and education programs are keeping traditional practices alive. Technology is also offering new ways to preserve our heritage. We need to find a balance between development and preservation. If we work together and take pride in our heritage, we can ensure it continues to inspire future generations. This paper aims to explore the importance of preserving India’s cultural heritage, examine the challenges faced in its protection, and highlight the efforts and strategies currently in place to address these challenges.